Conversations for providers caring for patients with rectal cancer: Comparison of long‐term patient‐centered outcomes for patients with low rectal cancer facing ostomy or sphincter‐sparing surgery. (21st March 2016) - Herrinton, Lisa J.; Altschuler, Andrea; McMullen, Carmit K.; Bulkley, Joanna E.; Hornbrook, Mark C.; Sun, Virginia; Wendel, Christopher S.; Grant, Marcia; Baldwin, Carol M.; Demark‐Wahnefried, Wendy; Temple, Larissa K. F.; Krouse, Robert S.
Abstract : For some patients with low rectal cancer, ostomy (with elimination into a pouch) may be the only realistic surgical option. However, some patients have a choice between ostomy and sphincter‐sparing surgery. Sphincter‐sparing surgery has been preferred over ostomy because it offers preservation of normal bowel function. However, this surgery can cause incontinence and bowel dysfunction. Increasingly, it has become evident that certain patients who are eligible for sphincter‐sparing surgery may not be well served by the surgery, and construction of an ostomy may be better. No validated assessment tool or decision aid has been published to help newly diagnosed patients decide between the two surgeries or to help physicians elicit long‐term surgical outcomes. Furthermore, comparison of long‐term outcomes and late effects after the two surgeries has not been synthesized. Therefore, this systematic review summarizes controlled studies that compared long‐term survivorship outcomes between these two surgical groups. The goals are: 1) to improve understanding and shared decision‐making among surgeons, oncologists, primary care providers, patients, and caregivers; 2) to increase the patient's participation in the decision; 3) to alert the primary care provider to patient challenges that could be addressed by provider attention and intervention; and 4) ultimately, to improve patients' long‐term quality of life. This report includes discussion points for health care providers to use with their patients during initial discussions of ostomy and sphincter‐sparing surgery as well as questions to ask during follow‐up examinations to ascertain any long‐term challenges facing the patient.CA Cancer J Clin 2016;66:387–397. © 2016 American Cancer Society.